Dynamic Power Flow Cascading Failure Analysis of Wind Power Integration with Complex Network Theory - Yushu Sun; Xisheng Tang; Guowei Zhang; Fufeng Miao; Ping Wang (Energies, 2017)
The impact of the rapid development of large-scale centralized wind power farms on the power system is drawing more and more attention. Some topics about grid-connected wind power are discussed from the view of complex network theory in this paper. Firstly, a complex network cascading failure model is established, combined with dynamic AC power flow (DACPF). Then, the IEEE 30 bus system is used to analyze its validity using the simulations of nodes removal, wind power integration, as well as the change of current and voltage boundaries. Furthermore, the influences of wind power before and after smoothing are investigated. Also, different wind power coupling locations are studied. Finally, some significant conclusions are obtained to provide references for large-scale wind power integration.